Oral presentation skills among low proficiency ESL undergaduates / Zeuricca Johnny Majamin - Zeuricca Johnny , Majamin (2020)
This research study seeks to examine the issues that are related to ‘Oral Presentation Skills among Low Proficiency ESL Undergraduates’. The two research questions that have been constructed in this study focuses on eliciting the perspective of low proficiency undergraduates on the types of oral presentation difficulties that are faced by them and the types of communicative strategies that are used by this group in coping with their oral presentation difficulties. A total of fifty one low proficiency undergraduates from 3 local private universities with a MUET score of Band 1 and Band 2 have participated as respondents for the questionnaire on oral communication strategy inventory (OCSI) that has been adapted from Nakatani’s (2006) framework. From the total number of participants, thirteen of them were selected for an individual interview session to understand their views on the types of difficulties and challenges that are faced by them when giving an oral presentation. The interview was a semi structured interview where the questions that were posed had been carefully constructed with reference to Dornyei and Scott’s 1997 framework. The findings emphasises that despite facing similar types of difficulties as listed in Dornyei and Scott’s (1997) study, this particular group of undergraduates also faces difficulties in aspects involving affective factors and topical knowledge. In terms of the type of strategies that were used, fluency oriented strategies was revealed to be the most used strategy based on the rankings of all the 8 strategies that were listed, while message abandonment strategies had been ranked the lowest and the least used strategy among them. The findings generated from this study would benefit lecturers in understanding the challenges that are faced by undergraduates in terms of oral presentation. This would help lecturers to choose and improve on their teaching approaches and methods that were used in ESL lessons to fit the learning style and needs of ESL undergraduates especially those from the low proficiency group. By exposing students with a variety of communication strategies, it could help students to overcome their difficulties in doing an oral presentation.